Clonal multiplication of the cinchona tree (Cinchona officinalis): an alternative to conserve the national tree of Peru (Bioagro, 2021)
The cinchona tree (Cinchona officinalis), an emblematic species of Peru, has for many years been threatened with extinction. The objective of this study was to evaluate the influence of the type of mini-stake (apical and basal) and the absorption time of indole-butyric acid (0, 2, 6, and 10 minutes) on the clonal multiplication of the cinchona tree. The shoots were collected from trees of natural populations present in the Conila-Peru montane forest, at an altitude of 2800 m. The mini-cuttings, basal and apical, were treated with indole butyric acid at 2000 mg·L-1 and were left to rest for different times. The data were subjected to an analysis of variance and the means were compared with the Tukey test. After 60 days, it was found that the basal mini-cuttings presented a significantly higher rooting percentage (54.77 %) compared to the apical mini-cuttings (40.10 %), being also higher in survival (62.75 %) and size of roots (17.38 mm). The absorption times of 6 and 10 minutes turned out to be the most outstanding, while the  control  (0 minutes)  turned  out  to  be  the  lowest  treatment.  In  conclusion,  the  basal  mini-cuttings  and  the  absorption times of 6 and  10  minutes  turn  out  to  be  the  most  appropriate  to  guarantee  the  rooting  of  mini-cuttings  of  the  cinchona  tree.
Keywords: Indole butyric acid; plagiotropic shoots; rooting; vegetative propagation